PENGARUH CORPORATE ENTREPRENEURIAL INTENTION DAN SELFEFFICACY TERHADAP ENTREPRENEURIAL INTENTION DAN ORGANIZATIONAL PERFORMANCE - Okto Aditya Suryawirawan (Jurnal Ekonomi dan Bisnis Airlangga, 2019)
Introduction: This study aims to examine the effect of corporate entrepreneurial intentions consisting of innovation, risk taking, and proactiveness on entrepreneurial intentions and organizational performance, with self-efficacy as a variable that moderates the influence between corporate entrepreneurial intentions and entrepreneurial intentions in Citraland Surabaya.Methods: This study uses quantitative methods and the samples used are employees from various departments at Citraland Surabaya. The instrument used in this study was a questionnaire, then tested the relationship between variables with partial least squares, using the SmartPLS software.Results: The results of this study indicate that there is a positive and insignificant effect of innovation on entrepreneurial intentions, a negative and insignificant effect of risk taking on entrepreneurial intentions, and a non-significant positive effect on entrepreneurial intentions. This study also found that the overall variables of corporate entrepreneurial intention had a positive and insignificant effect on organizational performance. The moderator variable in the form of selfefficacy was found to be unable to moderate the effect of the company's entrepreneurial intentions on entrepreneurial intentions.Conclusion and suggestion: The company can also facilitate the entrepreneurial interest of these employees by giving them higher authority when the company establishes new branches. It is hoped that the company will realize the importance of fostering interest in the company, and how this will provide them with future retirement.